How to be both - Ali Smith
"SHORT-LISTED FOR THE MAN BOOKER PRIZE Passionate, compassionate, vitally inventive and scrupulously playful, Ali Smith's novels are like nothing else. How to be both is a novel all about art's versatility. Borrowing from painting's fresco technique to make an original literary double-take, it's a fast-moving genre-bending conversation between forms, times, truths and fictions. There's a renaissance artist of the 1460s. There's the child of a child of the 1960s. Two tales of love and injustice twist into a singular yarn where time gets timeless, structural gets playful, knowing gets mysterious, fictional gets real--and all life's givens get given a second chance"--
"The brilliant Booker-nominated novel from one of our finest authors: How to Be Both is a daring, inventive tale that intertwines the stories of a defiant Renaissance painter and a modern teenage girl. How can one be both--near and far, past and present, male and female? In Ali Smith's new novel, two extraordinary characters inhabit the spaces between categories. In one half of the book, we follow the story of Francescho del Cossa, a Renaissance painter in fifteenth-century Italy who assumes a duel identity, living as both a man and a woman. In the novel's other half, George, a contemporary English teenage girl, is in mourning after the death of her brilliant, rebellious mother. As she struggles to fill the void in her life, George finds her thoughts circling again and again around a whimsical trip she and her mother once made to Italy, to see a certain Renaissance fresco... These two stories call out to each other in surprising and deeply resonant ways to form a veritable literary double-take, bending the conventions of genre, storytelling, and our own preconceptions"--
Keywords: Artists -- Italy -- Fiction; Art, Italian -- Fiction; Gender identity -- Fiction; Teenage girls -- Fiction; Novel English; Literature English; Literature